Clinical and Demographic Features of Pediatric-Onset Behcet's Disease and Evaluation of Optical Coherence Tomography Findings - Balbaba, Mehmet; Ulas, Fatih; Postaci, Sevinc Arzu; Celiker, Ulku; Gurgoze, Metin Kaya (Taylor & Francis Inc, 2020)
Purpose: To evaluate the clinical characteristics, including spectral domain optical coherence tomography (SD-OCT) findings, of pediatric-onset Behcet's disease (PBD) patients. Methods: Medical records of 23 PBD (15 males and 8 females) and 24 (15 males and 9 females) healthy subjects were evaluated retrospectively. The main outcomes were compared between PBD patients, with and without ocular involvement, and healthy subjects. Results: The mean age at onset was 12.00 +/- 2.10 years. Mean follow-up period was 25.17 +/- 15.36 months (range 6-48). Retinal vasculitis was the most common ocular finding (7 patients). Most of the complications of systemic treatment were associated with long term corticosteroid therapy. There was no significant difference between the mean retinal thickness of the PBD patients and healthy controls (p > 0.05). The mean choroidal thickness was significantly increased in all measured segments of PBD patients with ocular involvement (p < 0.01). Conclusion: Choroidal thickness of PBD patients with ocular involvement was significantly thicker compared to the PBD patients without ocular involvement and to healthy control subjects.
Keywords: Behcet's disease; choroidal thickness; optical coherence tomography; pediatric-onset Behcet's disease; retinal thickness